Active Construction of Profession-Related Events: The Priming Effect among Pre-service Teachers with Different Professional Identity - Wang, Xin-qiang; Zhu, Jun-cheng; Liu, Lu; Chen, Xiang-yu; Huo, Jun-yu (Frontiers in Psychology, 2018)
Pre-service teachers with different professional identity may actively construct different subjective profession-related events based on the same objective profession-related events. To explore the priming effect among pre-service teachers with different professional identity, this study examined the effect of positive, negative, or neutral priming sentences in an individualized narration of profession-related events through a priming paradigm. Forty-two female volunteers were asked to complete positive, negative, and neutral priming sentences describing profession-related events. The results showed that, relative to those with weak professional identity, participants with strong professional identity generated a higher number of positive items when primed with different stimuli and displayed greater positive priming bias for positive and neutral stimuli. In addition, relative to those with strong professional identity, participants with weak professional identity generated a higher number of neutral and negative items when primed with positive and negative stimuli, respectively, and displayed greater negative priming bias towards negative stimuli. These results indicate that pre-service teachers with strong professional identity were likely to have established positive self-schemas involving profession-related events, which facilitated active, positive construction of such events.